Optimization of asphalt rubber hot mixes based on performance laboratory tests - Neto, Silvrano Adonias Dantas (2003)
Asphalt binders modified with crumb rubber recycled from ground tires have been successfully used in asphalt mixtures improving the mechanical and functional behaviour of the pavements. This paper shows the influence of several factors that affect the behaviour of asphalt-rubber (AR) and of hot mixes made with this material. Modified binders were prepared using a straight binder with 35/50 penetration and rubber obtained by the environmental process. Samples of asphalt-rubber were collected at different digestion time and temperature and conventional characterization tests were performed. Gap-graded hot mixes were prepared using 8% of modified AR binder and resilient modulus and fatigue tests were carried out. Tests with the modified binder showed a great influence of the rubber content, digestion time and temperature in the asphalt-rubber behaviour. The results of mechanical tests revealed that an increase of rubber content enhances fatigue life and decreases the resilient modulus of the asphalt mixes studied.